2009
DOI: 10.1007/s11802-009-0089-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicity effect of benzo[α]pyrene on scallop Chlamys farreri

Abstract: The toxic effects of benzo[α]pyrene (B[α]P) at different concentrations (0.1, 0.5, 1, 2.5 and 7.5 μgL -1 ) on scallop (Chlamys farreri) immune system were studied. The results showed that B[α]P had significant toxic effects on the haemocyte counts, neutral red uptake, phagocytosis, bacteriolytic and antibacterial activity (P<0.05), while the seawater control and acetone control had no significant differences. The haemocyte counts, neutral red uptake, phagocytosis and bacteriolytic activity in all B[α]P treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…In this study, the pro-PO activity, PO activity, α 2 -M activity, antibacterial activity and bacteriolytic activity of the shrimps were significantly decreased following 6d exposure to high concentrations of BaP and CHR, and presented significant dose response and time response. These results were consistent with the studies of Liu [10] and Zhang [11], and they found that BaP and Aroclor 1254 could inhibit the humoral immune factors of scallop (Chlamys farreri).…”
Section: Effects Of Bap and Chr On Immune Parameterssupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, the pro-PO activity, PO activity, α 2 -M activity, antibacterial activity and bacteriolytic activity of the shrimps were significantly decreased following 6d exposure to high concentrations of BaP and CHR, and presented significant dose response and time response. These results were consistent with the studies of Liu [10] and Zhang [11], and they found that BaP and Aroclor 1254 could inhibit the humoral immune factors of scallop (Chlamys farreri).…”
Section: Effects Of Bap and Chr On Immune Parameterssupporting
confidence: 92%
“…Therefore, the THC in hemolymph was usually used as an important parameter to evaluate the immunotoxicity of pollutions [9]. In this study, the THC in hemolymph of the shrimps decreased significantly under 21d exposures to high concentrations of BaP and CHR, which agrees with the result of Zhang et al [11]. Previous work has indicated the susceptibility of its baseline immune parameters to the PAH phenanthrene, causing alterations in phagocytosis [28].…”
Section: Effects Of Bap and Chr On Immune Parameterssupporting
confidence: 90%
See 3 more Smart Citations